MAPPING OF CHROMITE OCCURRENCE IN A META-ULTRAMAFIC COMPLEX BY MAGNETOMETRIC PROSPECTING, SULRIOGRANDENSE SHIELD (SOUTHERN BRAZIL) - Ilha, Lenon Melo [UNESP]; Moreira, Cesar Augusto [UNESP]; Kumaira, Sissa; Guirelli Neto, Leonides [UNESP]; Masquelin, Henri (UNESP - Universidade Estadual Paulista, 2024)
This study presents the use of terrestrial magnetometry method in the characterization of a metamorphic and chromiummineralized ultramafic rocks in the São Sepé region (RS). The most preserved rocks are gray to dark green serpentinites and occasionally magnesian schists with folds and variable fracturing that occur as a lenticular body enclosed within the host meta-volcanosedimentary rocks. The chromite present in serpentinites is associated with magnetite and occurs in the form of small lenses. 1677 reading lines were made perpendicular to the main direction of the meta-ultramafic rock, with 25m spacing between measurement points. The magnetometric maps revealed high-intensity anomalies related to meta-ultramafic rocks. The results revealed the existence of highly magnetic individualized lenses orientated according to NE/SW. The direct relationship between high magnetization and chromite/ferro-chromite concentrations allows relatively detailed mapping of potentially mineralized areas, revealing dimensions more significant than the limits of the meta-ultramafic sequence defined in the geological map. The results indicate that the analytical signal amplitude map is a highly recommended product for planning sampling actions and reserve quantification, improving classical geological mapping.
MAPEAMENTO DE OCORRÊNCIA DE CROMITA EM COMPLEXO METAULTRAMÁFICO POR MEIO DE PROSPECÇÃO MAGNETOMÉTRICA, ESCUDO SUL-RIOGRANDENSE (SUL DO BRASIL)
Keywords: Analytical signal amplitude; Chrome; Magnetometry; Meta-ultramafic; Mineral research